Do seringal à universidade: o acesso das camadas populares ao ensino superior público no Acre - Maria do Socorro Neri Medeiros de Souza (2009)
This study problemizes the access to the public higher education in Acre, analyzing the presence of lower class people at UFAC and the constitution of school paths developed by youths from this social sectors that were admitted in the most selected courses of this institution (Medicine and Law), overcoming the adverse conditions and the high selectivity. The research has utilized quantitative and qualitative procedures that became operational in two stages. The first stage constituted a statistical treatment of the data base about the students admitted in 2008. It was identified their socioeconomic profile and it was made a social x-ray of the academic field, in three levels: the institution, the course and the student. The second stage, which had a qualitative nature, constituted by twenty three interviews realized with seven students and sixteen people that have participated in their school paths. The research was based on the studies developed by Pierre Bourdieu and Bernard Lahire and on an ensemble of authors that made researches about unlikely statistics in Brazilian educational context. It was utilized the notion of social configuration, from Norbert Elias, as a model of intelligibility. So, the reports were submitted to vertical and traverse analysis, having as parameter five aspects previously defined: (a) the presence of the family on the sons school path, (b) the mobilization of the own individual; (c) senses attributed to education; (d) social and institutional references; (e) relation between the migratory process, the culture from the rubber plantation and the school path. In the vertical analysis, the singularity of each case was investigated and, in the transverse analysis, there were inquired aspects that make possible wide-ranging interpretations. The results showed that, although the students from popular ascendance occupy 60% of the vacancy in this university, their presence is much reduced on the most influential courses. This suggests a hierarchization of the academic field, reflecting the contrasts that exist on the society and the thesis of the excluded from the interior (BOURDIEU; CHAMPAGNE, 1998). The school biographies analysis made evident social configurations maintained by mobilization of students, of some families and, in some cases, of reference people that have proximity with the school universe. Therefore, the research suggests that there is a narrow relation between the nature and the intensity of the familys behavior, the mobilization of the students and the fluency and linearity of the school path.